Right Frontal White Matter and Tourette Syndrome - J Gordon Millichap (Pediatric Neurology Briefs, 2002)
An MRI volumetric analysis of frontal and nonfrontal gray and white matter was performed in 11 boys with Tourette syndrome (TS) only, 14 with TS + ADHD, 12 with ADHD only, and 26 healthy boys, at the Kennedy Krieger Institute, Baltimore, MD.